A Review on the Management of Hip and Knee Osteoarthritis. (28th September 2013) - Wood, Alexander MacDonald; Brock, Timothy M.; Heil, Kieran; Holmes, Rachel; Weusten, Axel
Abstract : Arthritis is the most common chronic condition affecting patients over the age of 70. The prevalence of osteoarthritis increases with age, and with an aging population, the effect of this disease will represent an ever-increasing burden on health care. The knee is the most common joint affected in osteoarthritis, with up to 41% of limb arthritis being located in the knee, compared to 30% in hands and 19% in hips. We review the current concepts with regard to the disease process and risk factors for developing hip and knee osteoarthritis. We then explore the nonsurgical management of osteoarthritis as well as the operative management of hip and knee arthritis. We discuss the indications for surgical treatment of hip and knee arthritis, looking in particular at the controversies affecting young and obese patients in both hip and knee replacements. Patient and implant related outcomes along with survivorships are addressed as well as the experiences and controversies described in national joint registries.